DEVELOPMENT OF A QUALITY ASSURANCE FRAMEWORK FOR SIMULATOR DEVELOPMENT: INTEGRATION OF CUTTING-EDGE THEORIES AND BEST PRACTICES (SYSTEMATIC LITERATURE REVIEW 2020–2025) - Ekanesti Ruswidia Sari; Heriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study presents a Quality Assurance (QA) framework for simulator development, integrating the theories of Total Quality Management (TQM), ISO 25010, Capability Maturity Model Integration (CMMI), and Agile Quality Assurance. A systematic literature review (SLR) was conducted on peer-reviewed publications and internationally accredited standards in Scopus from 2020 to 2025. The results of the review indicate that QA for simulator development must be multidimensional: user-oriented design, continuous improvement, software reliability, verification and validation (V&V), and data-driven feedback. The proposed QA framework was validated through benchmarking of best practices and the latest industry standards, with the aim of improving the reliability and effectiveness of next-generation simulators.